2017
DOI: 10.1038/tp.2016.290
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3R receptor activation in the dorsal striatum triggers stereotypies in a mouse model of tic disorders

Abstract: Tic disorders affect ~5% of the population and are frequently comorbid with obsessive-compulsive disorder, autism, and attention deficit disorder. Histamine dysregulation has been identified as a rare genetic cause of tic disorders; mice with a knockout of the histidine decarboxylase (Hdc) gene represent a promising pathophysiologically grounded model. How alterations in the histamine system lead to tics and other neuropsychiatric pathology, however, remains unclear. We found elevated expression of the histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 56 publications
2
68
0
Order By: Relevance
“…Locomotor activity was assessed using an open field apparatus (Omnitech Electronics) as described previously (37, 38). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Locomotor activity was assessed using an open field apparatus (Omnitech Electronics) as described previously (37, 38). …”
Section: Methodsmentioning
confidence: 99%
“…Following behavioral testing, brains were removed, fixed, sliced, and immunostained as described previously (37, 38, 45, 46). …”
Section: Methodsmentioning
confidence: 99%
“…In our laboratories, we have used a range of methods to quantify repetitive movements, including manual scoring from videos (Castellan Baldan et al, 2014; Pogorelov et al, 2015; Xu et al, 2015a; Xu et al, 2015b; Xu et al, 2016), automated scoring from videos (Rapanelli et al, in press; Xu et al, 2015a), and repetitive beam-breaks in an open field (Rapanelli et al, 2017; Rapanelli et al, in press). Standardization is needed; however, in light of the discussion above, standardized approaches to quantification of behavioral pathology need to be somewhat flexible – the precise topography of tic-relevant movements may not be identical across models and across contexts.…”
Section: Studying Tic-like Movements Using a Phenomenological Approachmentioning
confidence: 99%
“…Hdc -KO mice also show impaired PPI (as do TS patients carrying a mutated Hdc allele), providing further validation (Castellan Baldan et al, 2014). Parallel studies in these mice and in patients carrying the Hdc mutation have identified abnormalities in DA modulation of the striatum and in dopamine D2/D3 receptors in the substantia nigra as a potential locus of pathology and/or homeostatic regulation in tic disorders (Castellan Baldan et al, 2014; Rapanelli et al, 2017; Rapanelli et al, 2014). …”
Section: Modeling Tics Based On Specific Pathophysiological Hypothesesmentioning
confidence: 99%
“…The H 3 R agonist immepip has not been found to affect intra-striatal DA levels in wild-type mice (Alfaro-Rodriguez et al, 2013). Similarly, systemic administration of the specific agonist R-aminomethylhistamine (RAMH), at doses that produce behavioral effects (see below; Rapanelli et al, in press), does not produce the predicted reduction in striatal DA – in fact, in KO mice it produces a small but significant elevation in DA after RAMH challenge (Rapanelli et al, in press; Rapanelli et al, 2016). The ability of both endogenous and exogenous HA to reduce striatal DA levels (Castellan Baldan et al, 2014) can be concluded to depend on different receptors.…”
Section: Introductionmentioning
confidence: 99%